Using the Artificial Gas Lift to Increase the Productivity of Noor Oil Field / Mishrif Formation - Salh, Talib A.; Sahi, Safaa H.; Ismael, Shaymaa A. Hussein (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
Noor Oil Field is one of Iraqi oil fields located in Missan province / Amarah city. This field is not subjected to licensing rounds, but depends on the national effort of  Missan Oil Company. The first two wells in the field were drilled in seventies and were  not opened to production until 2009. The aim of this study is to study the possibility of using the method of gas lift to increase the productivity of this field . PROSPER software was used to design the continuous  gas lift by using maximum production rate in the design.   The design was made after comparing  the measured pressure with the calculated pressure, this comparison  show  that the method of Beggs-Brill and Petroleum Expert2 gave the best results; therefore, these correlations have been adopted in the design of gas lift.   The  point  of gas injection had been selected;  the optimum  gas injection  rate, the  maximum  oil production rate, the number of valves required for gas injection and their  depth, the  pressure required to open and close each valve  were calculated. The effect of  water-cut, change the amount of ratio of gas to oil and decline  reservoir  pressure in natural flow case and  gas lift  method case were studied. The results of gas lift design show that the maximum oil production rate is (1000) STB/Day and the optimum gas injection rate (2.65) MM Scf/Day at using  operating pressure of (1700) psi available at casing head and the minimum bottom hole  following pressure  is (1501.5) psi.